Preparation of Nano-Metal-Oxide Incorporated Biochar for Remediation of Water Pollution - Arar, Özgür (Current Nanomaterials, 2025)
BackgroundBecause of its numerous advantages, biochar has been widely used to remove contaminants from aqueous media for several years. However, unmodified biochar often exhibits low sorption capacity. Therefore, various nano-sized metal oxides have been developed to modify biochar and improve its ability to remove impurities.ObjectiveThis review aims to provide information on preparing and applying biochar loaded with nano-sized metal oxides to treat pollutants in water samples.ResultsRaw biochar has limited applicability/capacity for certain pollutants, such as inorganic anions. However, modification with metal oxides improved removal performance, sorption capacity, and selectivity.ConclusionBiochar loaded with metal oxides is believed to be an environmentally friendly alternative for treating polluted water. Selective sorbents with high capacity and fast kinetics towards undesirable solutes can be produced using suitable metal oxides. The sorbent can remove pollutants from solutions with a high removal rate.
Keywords: ion exchange